Life on the frontline of COVID-19: Jean's story. (2nd April 2021) - Ellis, Karen
Abstract : Jean Ryder moved to Royal Star & Garter, Surbiton, in 2014, accompanied by her WWII and RAF veteran husband. She died in May 2020, following a positive COVID-19 test. As the nation commemorates the anniversary of the first lockdown with a National Day of Reflection, Jean's daughter Karen Ellis remembers her parents' time at the Home, her mother's sudden death, and why she is still waiting for closure.